Teledermatología sincrónica en tiempos de Covid-19. Percepción del dermatólogo - Manubens V., Víctor; Zemelman D., Viviana (Revista Hospital Clínico Universidad de Chile, 2023)
Teledermatology (TD) is a remote medical care tool that experienced a great boom during the COVID19 pandemic, resulting in an increase in both, the number of remote consultations and the number of dermatologists who practice it. Several studies have reported a high degree of satisfaction among patients attended by this method. However, few studies have done so in dermatologists. We set out to investigate the experience of Chilean dermatologists with the tool by means of an online survey. Results. A total of 156 surveys were completed. The number of dermatologists using TD increased from 19.9% to 80.8% during the pandemic. They cited the absence of the physical examination-dermatoscopy as the main limitation to developing TD and reported feeling more comfortable with some pathologies. Dermatologists feel moderately comfortable and confident with the tool, however, they experienced varying degrees of stress and frustration. Only 40.8% plan to continue using TD in the future. Conclusion. Synchronous TD has clear limitations, however, these should emerge as an opportunity to consider in its development and its platforms, in order to generate a more comfortable tool for more dermatologists and thus extend its use, as an important tool for equal access to health care in Chile.